Implementasi Algoritme Forkskinny pada Pengiriman Data Antara IoT Node dengan IoT Gateway - Buntoro Tirto Sugondo; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Internet of things is an interesting topic, especially on data security, besides that the limited resources of IoT devices are a challenge for data encryption and authentication processes. Due to the rapid development of IoT, the National Institute of Standards and Technology (NIST) launched a project that aims to determine a lightweight cryptography standard, one of the candidates is forkskinny (ForkAE) which is a lightweight cryptography that uses a new scheme for authentication encryption (AE) based on skinny. In this work, the implementation of the forkskinny algorithm is carried out to secure the data between the IoT node and the IoT gateway, from the results of the tests that have been done, the results are obtained. Memory allocated by the IoT node for data encryption and decryption requires an average SRAM of 27568 bytes of the total SRAM 81920 bytes so that the average percentage of SRAM used is 33.6523% and for flash memory has an average of 268097.6 bytes with total flash memory of 1044464 bytes so it only requires a flash memory percentage of 25.6684%. The algorithm performance test on the IoT node obtained an average of 4128.53333 microseconds, for the encryption and decryption process an average of 5858.13333 microseconds was obtained. The algorithm performance on the IoT gateway for the encryption process has an average of 1149.8 microseconds and for data decryption the average value is 1676.7 microseconds.